Disparities in maternal knowledge and practices on sleep training: a cross-sectional analysis of urban vs. rural areas - Rambey, Kinandra Rafa Khalisha; Gunawan, Talitha Dinda; Sekartini, Rini (Frontiers in Sleep, 2025)
BackgroundQuality sleep is crucial for the growth and development of children. Sleep training is an effective method to improve the sleep quality of young children. This study aims to identify the knowledge and practices of mothers regarding sleep training for young children in Indonesia.MethodsThis cross-sectional study included 417 mothers of children aged 3–36 months recruited purposively from three healthcare facilities in Indonesia, two urban and one rural, between March and June 2024. Data on sociodemographic characteristics, maternal knowledge, and maternal sleep-training behaviors were collected using validated, structured questionnaires. Item reliability and content validity were assessed through expert review and pilot testing. Descriptive, bivariate, and multiple linear regression analyses were performed using continuous knowledge and behavior scores, with co-sleeping variables included in sensitivity analyses. Mixed-effects linear models with random intercepts by site were applied to account for facility-level clustering and to assess model robustness.ResultsHigher maternal education, formal employment, and higher socioeconomic status were significantly associated with greater knowledge and behavior scores. Mothers residing in urban areas demonstrated significantly better sleep-training practices, whereas knowledge scores did not differ between urban and rural participants. Multiple regression analyses confirmed that education level, employment type, and socioeconomic status independently predicted knowledge scores, while employment type, socioeconomic status, and urban residence independently predicted behavior scores. Mixed-effects modeling indicated that site-level clustering accounted for approximately 47% of variance in knowledge and 35% in behavior scores, with model comparisons (AIC/BIC) confirming robustness across specifications. Sensitivity analyses adjusting for co-sleeping and household crowding yielded consistent findings, indicating that the main associations were not affected by these contextual variables.ConclusionMothers with higher education, formal employment, and greater socioeconomic status demonstrated better knowledge and sleep-training behaviors; however, knowledge was not directly associated with practice. These findings highlight that improving maternal understanding alone may be insufficient to change behavior without addressing sociocultural norms—particularly widespread co-sleeping and household constraints—that influence sleep practices. Tailored, context-sensitive educational interventions are needed to promote consistent and developmentally appropriate sleep routines for young children in Indonesia.